Kesehatan Lingkungan Sekolah Dasar Negeri Mlilir di Kecamatan Dolopo Kabupaten Madiun tahun 2017 - Ayu Purwanti; Rusmiati .; Sri Mardoyo (Poltekkes Kemenkes Surabaya, 2018)
ABSTRACTSchool is one of public places, where the public places have potency as a place of disease transmission occurrence, environmental pollution or other health problems. Based on preliminary survey conducted in Mlilir State Elementary School on Dolopo District Madiun Regency which the number of school was 2 schools, it was known that both of schools were located in Mlilir Community Health Centre area which the incidence rate of diarrhea was the highest in Madiun Regency area in 2015 – 2016. Mlilir State Elementary School was located on the edge of the highway which had potency of air contamination either in form of gas/fume or dust particles. Moreover, the environmental cleanliness of Mlilir State Elementary School was still less good. The aim of this study is to determine the environmental health of Mlilir State Elementary School on Dolopo District Madiun regency in 2017.This study was a descriptive study in form of survey. The object that studied in this study include school location, school yard, building construction (roof and gutters, ceilings, walls, floor, and doors), room building (classrooms, teacher rooms, School Health Unit room, library and place of worship, air quality (measurement of dust concentration in front of classrooms), illumination, ventilation, sanitation facilities (clean water supply, toilets, sewage disposal facilities and garbage disposal facilities). The instruments used were interview forms, assessment forms, lux meter, sound level meter, high volume dust sampler, measuring tape, pH indicator strip paper. Data were analyzed descriptively.The results of study showed that the environmental health of Mlilir State Elementary School on Dolopo District Madiun Regency in 2017 was categorized as Enough. All people of Mlilir State Elementary School must always keep the cleanliness of school environment and repair school facilities and infrastructures which do not meet the requirements.Keywords : Environmental Health, Elementary School.